Expiratory Flow – Vital Capacity: Airway – Lung Dysanapsis in 7 Year Olds Born Very Preterm? - Ioan, Iulia; Gemble, Aurore; Hamon, Isabelle; Schweitzer, Cyril; Metche, Stéphanie; Bonabel, Claude; Nguyen-Thi, Phi L.; Hascoet, Jean-Michel; Demoulin-Alexikova, Silvia; Marchal, François (Frontiers in Physiology, 2018)
An index normalizing airway dimension for lung size derived from spirometry was found inversely correlated to lung size in school children born very preterm, indicating larger alveolar volumes draining into comparatively smaller airways, in contrast with children born full term where the index was independent of lung size.